2022
DOI: 10.1038/s41368-022-00200-5
|View full text |Cite
|
Sign up to set email alerts
|

IFT140+/K14+ cells function as stem/progenitor cells in salivary glands

Abstract: Stem/progenitor cells are important for salivary gland development, homeostasis maintenance, and regeneration following injury. Keratin-14+ (K14+) cells have been recognized as bona fide salivary gland stem/progenitor cells. However, K14 is also expressed in terminally differentiated myoepithelial cells; therefore, more accurate molecular markers for identifying salivary stem/progenitor cells are required. The intraflagellar transport (IFT) protein IFT140 is a core component of the IFT system that functions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Keratin 14 is expressed in adult myoepithelial cells, but in addition, according to Adhikari et al, CKs 14 and 18 could also be found in acinar cells during acinar cell development (Adhikari et al 2018 ). We detected keratin 14 because Keratin-14 + (K14 + ) cells have gained increasing attention given that they are stem/progenitor cells that are actively involved in salivary gland development, homeostasis maintenance, and regeneration following injury (Zhang et al 2022 ). Furthermore, Kusama et al mentioned that CK18 was detected in the cytoplasm of acinar/ductal cells in normal human salivary glands (Kusama et al 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Keratin 14 is expressed in adult myoepithelial cells, but in addition, according to Adhikari et al, CKs 14 and 18 could also be found in acinar cells during acinar cell development (Adhikari et al 2018 ). We detected keratin 14 because Keratin-14 + (K14 + ) cells have gained increasing attention given that they are stem/progenitor cells that are actively involved in salivary gland development, homeostasis maintenance, and regeneration following injury (Zhang et al 2022 ). Furthermore, Kusama et al mentioned that CK18 was detected in the cytoplasm of acinar/ductal cells in normal human salivary glands (Kusama et al 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…May et al showed that CK14 + progenitor cells are fast-cycling cells that multiply in response to radiation-induced damage by persistent proliferation, and repopulate the granulated ducts by asymmetric division (May, et al, 2018). Zhang et al demonstrated that intra-flagellar transport (IFT + )/CK14 + stem/progenitor cells can promote gland regeneration by self-renewing and differentiating into granular ductal cells after duct de-ligation ( Zhang, et al, 2022 ). Hisatomi et al demonstrated that SMG duct ligation can induce the proliferation and expansion of Sca-1 + /c-Kit + stem cells to repair injury ( Hisatomi, et al, 2004 ).…”
Section: Salivary Gland Duct De-ligationmentioning
confidence: 99%
“…A recent study identified a combined marker, the intraflagellar transport protein 140 (IFT140) and keratin-14, for salivary gland stem/progenitor cells. 6 The authors elucidated IFT140 was essential for regulating salivary stem/progenitor cell differentiation and gland regeneration. In contrast, another study combining genetic pulse-chase experiments with single-cell clonal analyses and lineage-tracing analyses has shown that salivary gland homeostasis is maintained through acinar cell self-renewal by self-duplicating without a significant input from stem/progenitor cells.…”
Section: Introductionmentioning
confidence: 99%